2009
DOI: 10.1249/mss.0b013e3181857edo
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Intensity Interval Exercise on Lipid Oxidation during Postexercise Recovery

Abstract: These findings show that lipid oxidation during postexercise recovery was increased by a similar amount on two isoenergetic exercise bouts of different forms and intensities compared with the time-matched no-exercise control trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 29 publications
1
47
0
1
Order By: Relevance
“…This response was transient however in the current study as participants consumed a breakfast meal one hour after exercise and the resultant switch in metabolic fuel preference masked any more prolonged enhancement of fat oxidation which may otherwise have occurred. Specifically, other investigations have shown that lower RER values may persist for several hours after interval type exercise (McGarvey et al 2005;Malatesta et al 2008). The mechanisms responsible for this change in metabolism possibly include an elevated catecholamine response to HIIE which may stimulate mitochondrial respiration, lipolysis and fat oxidation (Mulla et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This response was transient however in the current study as participants consumed a breakfast meal one hour after exercise and the resultant switch in metabolic fuel preference masked any more prolonged enhancement of fat oxidation which may otherwise have occurred. Specifically, other investigations have shown that lower RER values may persist for several hours after interval type exercise (McGarvey et al 2005;Malatesta et al 2008). The mechanisms responsible for this change in metabolism possibly include an elevated catecholamine response to HIIE which may stimulate mitochondrial respiration, lipolysis and fat oxidation (Mulla et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Although research has been conducted to profile EPOC after continuous forms of exercise (Borsheim and Bahr 2003;LaForgia et al 2006), less attention has been given to high intensity forms of exercise (McGarvey et al 2005;Malatesta et al 2008). Specifically, how high intensity intermittent exercise (HIIE -representing one single bout of HIT) impacts upon EE and substrate utilisation, both during and after exercise, is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Compensatory rise in lipid oxidation after high intensity exercise High intensity exercise oxidizes almost exclusively CHO but is frequently followed by a compensatory rise in lipid oxidation which compensates more or less for the lipids not oxidized during exercise (Folch et al, 2001;Melanson et al, 2002), but it is inconsistent and frequently quite low (Malatesta et al, 2009;Lazer et al, 2010), even more if exercise is discontinuous (Warren et al, 2009). d. Long term regular exercise may increase the ability to oxidize lipids at rest Long term regular exercise may shift the balance of substrates oxidized over 24 hr toward oxidative use of higher quantities of lipids (Talanian et al, 2007).…”
Section: The Physiological Basis For Measuring Lipid Oxidation Duringmentioning
confidence: 99%
“…Similarly, 90 min of seated rest (Robinson and Haymes 1990) followed by 30 min (Cheuvront et al 2005;Havenith et al 1992;Robinson and Haymes 1990;Suzuki et al 1980) of moderate exercise (Cheuvront et al 2005;Flouris et al 2006Flouris et al , 2008Gavhed and Holmer 1996;Gavhed et al 1991;Ha et al 1998;Imamura et al 1998;Jay et al 2008;Kruk et al 1990;Nielsen and Endrusick 1992;Rissanen and Rintamaki 1997;Robinson and Haymes 1990;Suzuki et al 1980) and a 1-h recovery (Flouris et al 2006(Flouris et al , 2008Ha et al 1996) is well documented. Subjects maintained 60 revolutions per minute on the ergometer, which has been utilized in prior studies (Hellstrom et al 1970;Kenefick et al 2004b;Nielsen and Endrusick 1992;Suzuki et al 1980) to achieve an exercise intensity of 45-55% of VO 2max (Castellani et al 1999;Kenefick et al 2004a;Kruk et al 1990;Malatesta et al 2009;Nielsen and Endrusick 1992). All trials were conducted from 5:00 to 9:30 a.m. to maintain consistent circadian status.…”
Section: Experimental Trialsmentioning
confidence: 99%